A study of college students’ perceptions of utilizing automatic speech recognition technology to assist English oral proficiency - Liu, Jiaxin; Liu, Xianghu; Yang, Chuan (Frontiers in Psychology, 2022)
For English as a Foreign Language (EFL) students, automatic speech recognition (ASR) technology is the most potential assistant tool to help them improve their spoken English ability. The primary purpose of this study is to investigate learners’ perceptions towards ASR technology after it is applied to traditional classrooms. This study selected 249 English majors from a university in Northeastern China as samples and divided them into a control group consisting of 124 students and an experimental group including 125 students. The participants of two groups used ASR technology in the process of oral practice, and the experimental group also added teacher’s guidance compared with the control group. The teacher gives more detailed instruction in speaking based on the scores provided by ASR technology. Participants needed to complete relevant questionnaires and learning reflective journals during the experiment. The results of the study showed that both participants and instructors held positive and satisfactory attitudes towards the potential of ASR in oral training and believed that the technology could meet many of their needs such as the scoring system to help them more intuitively understand the real speaking level. The findings of this paper will give some implications to oral English teaching in the future.